THE IMPACT OF ESG PERFORMANCE AND BOARD SIZE ON FIRM PROFITABILITY - Rio Idris Timbul Simorangkir; Kepha Pondi; Lorina Siregar Sudjiman (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) performance and board size on firm profitability. ESG practices have become increasingly important as companies attempt to balance financial performance with social responsibility and sustainable development. The objective of this study is to examine whether ESG performance and board size influence firm profitability measured by Return on Assets (ROA). The study uses panel data collected from publicly listed firms with a total of 386 firm-year observations. Data were analyzed using panel regression techniques with control variables including firm size, leverage, and growth. The results indicate that ESG performance has a positive and significant impact on firm profitability. Companies that actively implement ESG practices tend to achieve better financial outcomes due to improved stakeholder relationships, enhanced reputation, and better risk management. Furthermore, board size is found to positively influence profitability, suggesting that larger boards may provide broader expertise and stronger monitoring mechanisms that enhance managerial decision-making. The findings contribute to the literature on corporate sustainability and governance by demonstrating that ESG engagement and board structure play an important role in improving financial performance. The study also provides practical implications for corporate managers and investors by highlighting the strategic importance of ESG integration and effective board composition in achieving sustainable profitability.